Intimate foreigners or violent neighbours? Thinking masculinity and post-apartheid xenophobic violence through film. Issue 2 (2nd April 2016) - Gqola, Pumla Dineo
Abstract: This article analyses post-apartheid public culture and two contemporary short films to build two arguments about the interplay of masculinity and violence in the 2008 and 2015 xenophobic outbreaks. The films are Xoliswa Sithole's Thandeka and Martine and Andy Spitz's Angels on our shoulders, both made as part of Filmmakers Against Racism's2008 interventions against xenophobic violence. I argue that 'foreigners' are made under conditions of perilous intimacy (not ignorance) and that feted forms of post-apartheid masculinity enable negrophobic/Afrophobic xenophobic violence.